Attitudes of health care professionals towards interprofessional teamwork in Ashanti Region, Ghana - Edward T. Dassah; Veronica M. Dzomeku; Betty R. Norman; Daniel Gyaase; Mercy N. A. Opare-Addo; Kwame O. Buabeng; Yaw Adu-Sarkodie (BMC Medical Education, 2023)
Abstract Background Interprofessional collaboration ensures that high-quality health care is provided leading to improved health outcomes and provider satisfaction. Assessing the attitudes of health care professionals towards teamwork in Ghana is novel. Objective To examine the attitudes of health care professionals towards interprofessional teamwork and assess specific attributes influencing these attitudes in the Ashanti region, prior to implementing an in-service interprofessional HIV training programme. Methods A cross-sectional pre-training online survey using a modified Attitudes Toward Health Care Teams Scale was conducted among health care practitioners undergoing a two-day interactive interprofessional HIV training in Kumasi and Agogo from November 2019 to January 2020. Trainees were diverse health professional cadres selected from five hospitals in the Ashanti region of Ghana. Data was summarised using the mean and standard deviation for continuous variables, and frequencies and percentages for categorical variables. An exploratory factor analysis was conducted to categorise the 14 items of the modified attitudes scale. The Wilcoxon rank-sum (Mann–Whitney) and Kruskal–Wallis tests were used to test the mean attitude difference among the demographic characteristics. Statistical significance was set at p < 0.05. Results Altogether, 302 health professionals completed the survey. The ages ranged from 20–58 years, mean age 27.96 years (standard deviation 5.90 years). Up to 95% of the trainees agreed with the 14 statements on the modified attitudes scale. Three factors were identified; “quality of care”, “team efficiency”, and “time constraint” with Cronbach’s alpha measures of 0.73, 0.50, and 0.45 respectively. The overall mean attitude score was 58.15 ± 6.28 (95% CI, 57.42–58.88). Attitude of health care professionals towards interdisciplinary teams for patient care varied significantly by age (p = 0.014), health profession cadre (p = 0.005), facility (p = 0.037), and professional experience (p = 0.034). Conclusion Strengthening in-service interprofessional training for health practitioners especially early career professionals in the Ashanti region would be valuable.